Recasting NATO's Strategic Concept Possible Directions for the United States - Chivvis, Christopher S. (RAND Corporation, 2009)
The revision of the North Atlantic Treaty Organization's strategic concept offers an excellent opportunity to build an alliance capable of addressing the shared problems that its member states face. To spur debate over concrete problems, this paper examines five possible future directions for the alliance.